The “I” and selfhood in a collection of poetry on personal things: Symbolic Barthesian Studies - Muttafaqur Rohmah; Rizki Nurfida Pambayun; Titis Sugiyantiningtyas (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2025)
This study explores how children's ego and selfhood are portrayed in the poetry collection Hal yang Pribadi by M. Fatan DZ. The book was selected because its poems present children's voices in a unique and reflective manner. The research employs Roland Barthes’ theory of symbolic semiotics, particularly the concepts of denotation, connotation, and myth, to examine how meaning is constructed through words, imagery, and symbols in the poems. The analysis reveals that the narrative voice of “I” in the anthology is not neutral. Children’s identities in the poems are often shaped by social values such as family norms, gender roles, and adult expectations. The “I” in the poetry emerges as a figure in the process of self-formation yet is also guided by the symbolic systems embedded in language. This study concludes that children's poetry does more than convey beauty and moral messages—it serves as a symbolic space in which children's identities are negotiated and represented in relation to the surrounding world.